Different approaches for preparation of AuNPs-based conjugates as a signal-generating unit for electrochemical biosensors - Murasová, Pavla; Kovářová, Aneta; Srbová, Jana; Bílková, Zuzana (University of Pardubice, 2018)
With the advent of micro- and nanotechnology, major advances and breakthroughs have taken place in many areas, such as biotechnology, medicine, pharmacy or material industry. Gold nanoparticles (AuNPs) with their unique optical and physical properties as well as biocompatibility have already proved themselves to be powerful tool in biological applications. In this work, AuNPs were selected as a potential electrochemically active label. With the aim to use them as an electrochemical active tag, two types of AuNPs were tested and suitable protocols for their functionalization were optimized. Non-functionalized AuNPs were modified with thiolated DNA oligonucleotides using Au-S bond. Such conjugates could be potentionally used as a DNA probe. Functionalized AuNPs containing carboxyl groups were also modified, but with specific antibodies. In this case, the goal was to optimize suitable protocol for effective modification performed with carbodiimide crosslinker enabling direct and covalent immobilization. Finally, quality of AuNPs-IgG was defined by experiments via detection of bacterial cells in model samples.
Keywords: gold nanoparticles; bioconjugation; label; immunosensor